Assessing the needs of CSCL tool and its impacts in Malaysian context - Kasirun, Z.M.; Salim, S.S. (2008)
Reviewing on computer-supported collaborative learning (CSCL) tools revealed that CSCL is important to support collaborative learning (CL) strategy in school. Existing CSCL applications are mostly research-based and are not available for use. Through a survey on the needs for CSCL in Malaysia, it is confirmed that CSCL application is needed but the available one could not support CL activities. This paper discusses CSCL study in Malaysia, especially the relationship between user involvement and type of CSCL application needed. In particular, the CSCL application that could associate existing knowledge among students to build new knowledge for their better understanding and problem solving skills. We examine this need and assess its impact by developing Collaborative Environment for Teaching and Learning System (CETLs).